Comparative Analysis of Syntax and Semantics Sering with Jingchang - Chandra, Mei Rianto (ppjbsip, 2023)
The learning of a foreign language cannot be separated from an understanding of the structure and characteristics of that language, especially in terms of understanding grammar. This research aims to analyze the syntactic and semantic differences between the Indonesian word sering and the Mandarin wordç»å¸¸jingchang. The research method used in this writing is a qualitative method involving an analysis of two linguistic corpora, namely the Indonesian corpus and the Center for Chinese Linguistics PKU corpus. Based on the corpus data analysis, the results are as follows: 1. Sentence patterns and relationships between sentences in the Indonesian word sering can be used in declarative and interrogative sentence patterns; In sentence position, sering can be used in the middle of a sentence with the condition of use after verbs/adjectives that function as predicates. In informal usage, it can also be used at the beginning of a sentence, but not at the end of a sentence. In terms of synonym usage, the word sering can be used with action verbs, desires, existence, commands, decisions, and with adjectives indicating attitudes and feelings, but cannot be paired with adjectives indicating distance, form, and taste. 2. In terms of meaning, both the Indonesian word sering and the Mandarin wordç»å¸¸jingchang have the meaning of frequency and high intensity.Â AbstrakPembelajaran bahasa asing tidak dapat terlepas dari pemahaman akan struktur dan kekhasan bahasa tersebut, terutama dalam hal pemahaman akan tata bahasa. Penelitian ini bertujuan menganalisis perbedaan sintaksis dan semantik kata bahasa Indonesia sering dan bahasa Mandarinç»å¸¸jingchang. Metode penelitian yang digunakan dalam penulisan ini adalah metode kualitatif berupa analisis terhadap dua korpus linguistik, yakni korpus Indonesia dan Center for Chinese Linguistics PKU. Berdasarkan pada analisis data korpus, didapatkan hasil: 1. Pola kalimat dan hubungan antarkalimat pada kata bahasa Indonesia sering dapat digunakan pada pola kalimat deklaratif dan interogatif; Pada posisi kalimat, sering dapat digunakan pada tengah kalimat dengan syarat penggunaan setelah kata kerja/sifat yang berupa predikat, pada penggunaan informal, bisa juga digunakan pada awal kalimat, tetapi tidak dapat digunakan pada akhir kalimat; pada penggunaan padanan kata, kata sering dapat digunakan dengan kata kerja penanda tindakan, keinginan, keberadaan, memerintah, dan memutuskan, serta pada kata sifat penunjuk sikap dan perasaan, namun tidak dapat dipadankan dengan kata sifat penunjuk jarak, bentuk dan rasa. 2. Dalam segi makna, bahasa Indonesia sering' dan bahasa Mandarinç»å¸¸jingchang keduanya memiliki makna berulang dan intensitas tinggi.